Isozyme diversity of Citrus reticulata Blanco and Citrus limon (L.) Burm. f. of Nepal - Pahari, Shankar; Bimb, H.P. (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.16-20